COVID-19 diseases, understanding and treatments - Youngah Choi; Hyun-Ju Jin; Eun-Hyang Song; Bu-Yeon Kim; Shin-Ae Park (International Journal of Clinical Endocrinology and Metabolism - Peertechz Publications, 2023)
Seobuk Hospital is a hospital directly operated by the Seoul Metropolitan Government and has mainly served as a tuberculosis hospital. It is a Seoul city governmental public hospital which primarily provides inpatients and out patients treatment to the elderly, many of them suffering from dementia patients and the marginalized, such as the homeless and the disabled.  From March 2nd, 2020, to May 31th, 2022 Seobuk hospital was appointed to treat COVID-19 patients that required stationary treatment. South Korea's COVID-19 mortality rate has below 0.1% while in other countries such as the United States and in Europe the mortality rate varies between 1 and 2 %. We believe that it is due to the quarantine system which was put in place right from the start of the COVID-19 pandemic in Febuary 2020. Patients testing positive for COVID-19 were hospitalized free of charge and they were hospitalized usually in early period (2 - 3 days after COVID -19 testing) of COVID-19 disease.  In this paper we analyzed the disease patterns of patients hospitalized with COVID-19 using the data from the 4,531 patients charts which received treatment in Seobuk hospital between March 2nd, 2020 and May 31st, 2022 by looking at their clinical features and medication history and medications for treatment.  The key element of the guideline of our treatment was to administer Veklury (Remdesivir) or Paxlovid despite its high cost in the early period of the COVID-19 disease when oxygen saturation dropped below 94%. Nowadays we administer Veklury and Paxlovid right after COVID-19 is daignosed free of charge for the proper patient. It is believed that the current quarantine system in South Korea which allows patients to be treated with Veklury (Remdesivir) in hospitals at the initial stage of the infection and with an early Paxlovid administration in home treatment has contributed to lowering the death rate in South Korea.